P1093BENEFITS OF HOME HEMODIALYSIS. (6th June 2020) - Todorov Sakic, Verica; Djuric, Zivka; Djuric, Petar; Bulatovic, Ana; Popovic, Jovan; Naumovic, Radomir; Dimkovic, Nada
Abstract: Background and Aims: Home hemodialysis (HOHD) has been available as a modality of renal replacement therapy since the 1960s, in our center since 1972. Despite better patients' outcome provided by HOHD comparing to hospital hemodialysis (HHD), its adoption has been limited worldwide. The aim of this study was to compare anemia, nutrition, mineral metabolism and morbidity in patients on HOHD and HHD. Method: we analyzed dialysis and uremia related complications and morbidity in 19 HOHD patients in comparison with patients on HHD (N= 57). Each HOHD patient was previously matched with three patients on HHD by sex, age and reason for end stage renal disease (ESRD). Patients on HHD were on dialysis 3x4 h per week while patients on HOHD had dialysis on consecutive days in duration of 5-6 hours. Also, patients on HOHD were more frequent on hemodiafiltration (HDF), 89.5% of them, as compared to HHD patients (only 21.4%). Results: All patients on HOHD were using AVF as vascular access for HD, and most of the analyzed HHD patients (only 5.3% used AVG). As revealed by hemoglobin level (Hgb) patients on HOHD had significantly better anemia control than HHD patients (12±2.3 vs. 10.2±1g/dl, p=0.004), despite the lower ferritin level (94±117 vs. 256±175ng/ml, p=0, 001) and less frequent use of erythropoietin-stimulating agents (ESA), (and only 31% on HOHD vs 80% patients on HHD, p=0, 001). By analyzing patients that used ESA therapy, we revealed that HOHD patients had lower weekly dose of ESA (5333±3265 IU vs. 6068±4145 IU). The values of intact parathyroid hormone (iPTH), did not differ significantly between HOHD (311±419pg/ml ; min 5, 25, max 1529) and HHD (233±212pg/ml; min 19, 25, max 926), but higher percentage of patients in HOHD group underwent parathyroidectomy (63% vs. 3.5%). The average values of calcium, and phosphorus did not significantly differ between HOHD and HHD patients (2.4±0.3 vs. 2.3±0.2mmol/l; 1.5±0.5 vs. 1.6±0.5mmol/l, respectively). HOHD patients had significantly higher albumin level (43±4.5 vs. 40.6±4g/l, p=0, 035). There was no difference in annual hospital admission rate (0.4±0.5 vs. 0.6±0.7, p=0.35) between groups, but HHD patients had longer in-hospital stay. (4.8±5.3 days for HOHD vs. 7.3±9.3 days for HHD; p=0.16). Vascular access complications were most frequent reason for hospitalization in both groups (37%), followed by cardiovascular complications 13.6%, in HOHD group and infectious complications in HHD group 24%. Conclusion: Our study has shown that HOHD provides some advantages over HHD including better quality of life and better anemia and nutrition control, better control of parathyroid function and shorter in-hospital stay. More frequent and longer dialysis sessions may be possible reason including HDF.